Forest structure and tree stem carbon stock of Gambari Natural Forest Reserve, Oyo state, Nigeria (2019)
Tree stems are major above-ground carbon pools in the tropical forest structure. Forest structure creates micro-climatic conditions for various ecosystem services. Natural and man-made disturbances cause changes in forest structure. However, the effect of forest structure dynamics on stem carbon sequestration is yet to be clarified in Gambari Natural Forest Reserve, Oyo State, Nigeria. Understanding influence forest structure dynamics on stem carbon could improve prediction of carbon sequestration potential of Gambari Natural Forest Reserve. Therefore, the aim of this study was to quantify forest structure and stem carbon stocks in Gambari Natural Forest Reserve. Ten sample (30m×30m2) plots were randomly demarcated in Gambari Natural Forest using stratified random sampling method comprising 5 sample plots in each identified canopy structures; closed and open. Tree stems ≥10cm diameter-at-breast-height (dbh) were identified, enumerated and species diversity indices computed. Total height (TH) and diameter were also measured for volume and carbon estimation. Data collected were analyzed using descriptive statistics and ANOVA α0.05. A total of 50 tree species representing 25 families were identified in Gambari Natural Forest Reserve and closed canopy had higher diversity indices than open canopy structure. The lower and middle canopy class had the highest stems/ha in both structures. Diameter distribution of closed and open structure expressed extended reverse J-shaped and rotated sigmoid curves, respectively. Tree stem carbon stock were 0.66Mg/ha and 0.436Mg/ha in closed and open canopy structure, respectively. Microphyla pterigota (12.11%) and Triplochiton scleroxylon (25.84%) contributed highest carbon stock in closed and open canopy structures, respectively. The study concludes that the closed canopy structure of Gambari Natural Forest Reserve offers good option for carbon sequestration strategies as its structure and tree composition influences its stem carbon stock. However, only few tree species contributed to the high stem carbon stock in the study area. Therefore, these tree species can be considered in the establishment of carbon credit for carbon sequestration in Nigeria.